The senior cohousing handbook : a community approach to independent living. - Durrett, Charles, ....- (Gabriola Island : New Society, 2009)
No matter how rich life is in youth and middle age, the elder years can bring on increasing isolation and loneliness as social connections lessen, especially if friends and family members move away. Senior cohousing fills a niche for this demographic -- the healthy, educated and proactive adults who want to live in a social and environmentally vibrant community. These seniors are already wanting to ward off the aging process, so they are unlikely to want to live in assisted housing. Senior cohousing revolves around custom-built neighborhoods organized by the seniors themselves in order to fit in with their real needs, wants, and aspirations for health, longevity and quality of life. Senior Cohousing is a comprehensive guide to joining or creating a cohousing project, written by the U.S. leader in the field. The author deals with all the psychological and logistical aspects of senior cohousing, and addresses common concerns, fears, and misunderstandings. He emphasizes the many positive benefits of cohousing, including: > Better physical, mental, emotional and spiritual health > Friendships and accessible social contact > Safety and security > Affordability > Shared resources. Successful aging requires control of one's life, and this generation of seniors -- the baby boomers -- will find this book holds a compelling vision for their future.
Keywords: Woningbouw -- Ouderen